2013
DOI: 10.1073/pnas.1321160111
|View full text |Cite
|
Sign up to set email alerts
|

Fe-vacancy order and superconductivity in tetragonal β -Fe 1- x Se

Abstract: Several superconducting transition temperatures in the range of 30–46 K were reported in the recently discovered intercalated FeSe system (A1-xFe2-ySe2, A = K, Rb, Cs, Tl). Although the superconducting phases were not yet conclusively decided, more than one magnetic phase with particular orders of iron vacancy and/or potassium vacancy were identified, and some were argued to be the parent phase. Here we show the discovery of the presence and ordering of iron vacancy in nonintercalated FeSe (PbO-type tetragonal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…19 On the other hand, the variations of K atoms 6,36 probably serve as the major normal point pinning centers in K z Fe 2 Se 2 even though the lattice defects, e.g., Fe/Se vacancies cannot be totally excluded. 15,16,37,38 As shown in the insets of Fig. 2(b) and Fig.…”
Section: A)mentioning
confidence: 82%
“…19 On the other hand, the variations of K atoms 6,36 probably serve as the major normal point pinning centers in K z Fe 2 Se 2 even though the lattice defects, e.g., Fe/Se vacancies cannot be totally excluded. 15,16,37,38 As shown in the insets of Fig. 2(b) and Fig.…”
Section: A)mentioning
confidence: 82%
“…Therefore, considering the composition off-stoichiometry for the superconductivity of FeSe films, namely the vacancies or interstitial impurity 30,32 , we prepared the targets with subtle adjustment in the nominal Fe:Se, including 1:1.10, 1:1.05, 1:1.03, 1:1.00, 1:0.99, 1:0.97, 1:0.95, 1:0.90, and so on. For comparison, the films were grown with the same thickness of ~160 nm and on the same CF substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Since their discovery, iron-selenide SCs have been found to provide a strong platform for the investigation of their high-T c superconductivity, since they possess a simple structure, are nontoxic, and may be fabricated via numerous synthesis methods [2,18,33,34]. The simplest tetragonal β-Fe 1+δ Se (11-system) has T c ≈ 8.5 K at ambient pressure and is sensitive to chemical and physical pressure effects [35]. It was observed that T c can be increased up to 15 K in the β-Fe 1+δ Se system by partially replacing Se with Te and up to 36.7 K under the application of a hydrostatic pressure of 8.9 GPa [36,37].…”
Section: Introductionmentioning
confidence: 99%